1992
DOI: 10.1007/bf00968410
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of myelin proteins to a neutral endoproteinase: The degradation of myelin basic protein (MBP) and P2 protein by purified bovine brain multicatalytic proteinase complex (MPC)

Abstract: Multicatalytic proteinase complex (MPC) was isolated from bovine brain and the susceptibility of myelin basic protein (MBP) and P2 protein of bovine central and peripheral nervous system was examined. SDS-polyacrylamide electrophoretic analysis of purified MPC revealed protein bands of molecular weight ranging from 22-35 kDa. The enzyme is activated by SDS at a concentration less than 0.01%. Upon incubation with MPC, purified MBP and P2 proteins were degraded into smaller fragments. There was a 57% and 100% lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this study, we have also found that inhibiting proteasomes resulted in a delay in the myelin sheath degradation. This may be caused by direct inhibition of myelin protein degradation by proteasome inhibitors because the protein components of the myelin sheath such as myelin basic protein and peripheral myelin protein 22 are known to be substrates for the UPS (Fortun et al,2005; Lucas et al,1992) or by secondary results of the inhibition of Schwann cell dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have also found that inhibiting proteasomes resulted in a delay in the myelin sheath degradation. This may be caused by direct inhibition of myelin protein degradation by proteasome inhibitors because the protein components of the myelin sheath such as myelin basic protein and peripheral myelin protein 22 are known to be substrates for the UPS (Fortun et al,2005; Lucas et al,1992) or by secondary results of the inhibition of Schwann cell dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data also suggest that both wt Cot and trunc-Cot are catabolized via the proteasome in an ubiquitylation-independent manner. In this context, it should be stressed that although the vast majority of proteins need to be polyubiquitylated prior to proteasome degradation, other proteins that do not need to be polyubiquitylated for proteasome degradation are starting to be identified (3,15,36,39,50,60,66). However, the possibility that an isopeptidase activity could hydrolyze the polyubiquitin chain cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, cell markers of oligodendrocytes such as CNPase (2′,3′-cyclic nucleotide-3′-phosphodiesterase), APC (Adenomatous Polyposis Coli), O4 or Olig family proteins are used in immunohistochemistry to evidence the cell-specific loss in demyelinating-prone areas [44,48,66]. In addition, staining (e.g., luxol fast blue, eriochrome R cyanin) and protein markers such as MBP, PLP, MOG, MAG are used to characterize the demyelinating nature of the lesions, keeping in mind that histological stains showed less specificity towards myelin subcomponents and that myelin proteins may be more or less susceptible to rapid degradation following myelin attack [67,68].…”
Section: From a Myelinating Oligodendrocyte Pathologymentioning
confidence: 99%